NCAA Academic Reform - Michael Oriard (University of Kansas Libraries, 2012)
The purpose of this article is to offer a sociohistorical overview of academic reform in the National Collegiate Athletic Association (NCAA). To do so, the author draws heavily from football history and its association with academic reform in the broader intercollegiate athletics context. Intercollegiate athletics has undergone significant changes in professionalism and academic integrity over time-something that suggests the current dysfunctional structure can be systemically changed, too.